Does Physical Activity Reduce the Risk of Perceived Negative Health in the Smoking Population? - Iturra-Gonzalez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Background: Smoking is associated with poor health status. Increased prevalence of multiple diseases has been found in populations of smokers and ex-smokers. Physical activity (PA) could reduce the negative effects of smoking. Aims: To analyze the relationships between smoking and self-perceived health and between PA level and self-perceived health, according to the relationship with smoking in the Spanish population. To calculate the risks of perceiving negative health in relation to smoking, according to the PA level of the population. Hypothesis: A higher level of PA reduces the risk of perceiving negative health in the Spanish smoking population. Design and Methodology: Cross-sectional study with data from 17,708 participants, 15–69 years old, interviewed in the Spanish National Health Survey 2017. Intergroup differences were studied. Odds ratios (OR) and relative risks (RR) and their confidence intervals (95% CI) were calculated for negative self-perceived health. A Spearman’s rho correlation study was performed between the variables of interest. Results: Dependency relationships were found between self-perceived health and PA levels, in both genders and in different relationships with smoking (x2 < 0.001). Inactivity was related to higher prevalences of negative health perception (p < 0.05) in all groups analyzed. Inactive smokers (OR: 6.02. 95% CI: 3.99–9.07. RR: 5.24. 95% CI: 3.56–7.73) presented increased risks of negative health perception compared to people with low/medium PA levels, similarly found in other relationships with tobacco. Conclusions: Increasing the PA level of the smoking population could reduce the negative effects on their perceived health. Medium and high PA levels reduce the risk of negative health perception in the Spanish population, both in smokers, ex-smokers, and non-smokers. © 2022 by the authors.